2016
DOI: 10.7717/peerj.2048
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in the structure of a plant-frugivore network are influenced by bird migration and fruit availability

Abstract: Background. Ecological communities are dynamic collections whose composition and structure change over time, making up complex interspecific interaction networks. Mutualistic plant–animal networks can be approached through complex network analysis; these networks are characterized by a nested structure consisting of a core of generalist species, which endows the network with stability and robustness against disturbance. Those mutualistic network structures can vary as a consequence of seasonal fluctuations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 79 publications
(116 reference statements)
4
32
1
1
Order By: Relevance
“…This finding is consistent with the global meta-analysis that found that network specialization increased with decreasing resource availability at high latitudes (Schleuning et al 2012). Patterns of increasing specialization with decreasing resource availability can be explained by changes in frugivore behavior and frugivore specialization on specific, predictable resources (Ramos-Robles et al 2016, Dalsgaard et al 2017). The relationship was reversed on plots with high habitat structure.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with the global meta-analysis that found that network specialization increased with decreasing resource availability at high latitudes (Schleuning et al 2012). Patterns of increasing specialization with decreasing resource availability can be explained by changes in frugivore behavior and frugivore specialization on specific, predictable resources (Ramos-Robles et al 2016, Dalsgaard et al 2017). The relationship was reversed on plots with high habitat structure.…”
Section: Discussionsupporting
confidence: 89%
“…However in a more recent analysis an updated version of this Atlantic forest network was nested using a binary measure (Vizentin-Bugoni et al, 2016) Bascompte et al (2003) suggest that increases in the number of species in networks might result in greater nestedness. Sebastian-Gonzalez et al (2015) confirmed this increase in nestedness with greater number of species, but other studies found no such effect (Cuartas-Hernandez & Medel, 2015) or even reduced nestedness with increased number of species (Ramos-Robles, Andresen & Diaz-Castelazo, 2016). Indeed, when we reduced the network to only include species and observations that resulted in “legitimate” flower visits, we found nestedness values were lower although the network was still more nested than expected.…”
Section: Discussionmentioning
confidence: 68%
“…A high resource richness may be the cause of a low niche overlap between frugivores, because seeddispersal systems are known to be the less specialised compared to other types of mutualism such as plant-ant and plant-pollinator interactions (Blüthgen et al 2007). High fruit species richness reduces the overlap between the diets of frugivores because it reduces interspecific competition (Ramos-Robles et al 2016).…”
Section: Discussionmentioning
confidence: 99%